The impact of lending standards on default rates of residential real estate loans - Jo\~ao Gaudêncio; Agnieszka Mazany; Claudia Schwarz (European Central Bank (ECB), 2019)
This paper analyses the impact of lending standards for residential real estate (RRE) loans on default rates, using a novel loan-level dataset from the European DataWarehouse (EDW) that covers eight euro area countries. To the best of the authors' knowledge, this paper is the first to use, for this purpose, a consistent set of loan-level data on loans originated in multiple euro area countries. Previous literature has used either national loan-level data, which does not allow for cross-country comparisons, or aggregate cross-country data. The dataset is first explored through an extensive descriptive analysis and this is followed by static probit regressions. The findings confirm the key influence of lending standards - in particular, loan-to-value and loan-to-income ratios at origination, original loan maturity and borrower employment status - on loan default rates. The impact of other variables, such as interest rate fixation and payment type, varies depending on the country of loan origination. These results are particularly relevant for microprudential supervisors in their ongoing assessment of banks' credit policies. The highlighted country specificities should be taken into account in macroprudential policymaking.
Keywords: C25; G21; 330; loan defaults; lending standards; residential real estate; loan-level data; default probability